Comparative study of peritoneal adhesions after intraperitoneal implantation in rats of meshes of polypropylene versus polypropylene/polyglecaprone versus polyester/porcine collagen - Ribeiro,Waston Gonçalves (2019)
Abstract Purpose To Compare the extent and intensity of adhesions formed between the intra-abdominal organs and the intraperitoneal implants of polypropylene mesh versus polypropylene/polyglecaprone versus polyester/porcine collagen used for correction of abdominal wall defect in rats. Methods After the defect in the abdominal wall, thirty Wistar rats were placed in three groups (ten animals each) for intraperitoneal mesh implant: polypropylene group, polypropylene/polyglecaprone group, and polyester/porcine collagen group. The macroscopic evaluation of the extent and intensity of adhesions was performed 21 days after the implant. Results The polypropylene group had a higher statistically significant impairment due to visceral adhesions (p value = 0.002) and a higher degree of intense adherence in relation to polypropylene/polyglecaprone and polyester/porcine collagen groups (p value<0.001). The polyester/porcine collagen group showed more intense adhesions than the polypropylene/polyglecaprone group (p value=0.035). Conclusions The intraperitoneal implantation of polypropylene meshes to correct defects of the abdominal wall caused the appearance of extensive and firm adhesions to intra-abdominal structures. The use of polypropylene/polyglecaprone or polyester/porcine collagen tissue-separating meshes reduces the number and degree of adhesions formed.